Analysis of the Impact of Tax Reduction and Fee Reduction Policy on Chinas Economic Structure Optimization and Local Financial Risks - Zhang, Shuang (International Journal of Global Economics and Management, 2024)
This paper comprehensively analyzes the impact of tax reduction and fee reduction policies on the integration of Chinas digital economy and the real economy, the upgrading of industrial structure, local financial risks and other aspects. Research shows that tax cuts and fee cuts have generally promoted the optimization and upgrading of the economic structure, but the regional differences are significant, and the impact on local government debt risks is uncertain. The article suggests that tax and fee reduction policies should be adjusted according to the economic and social development, and the tax structure should be optimized to achieve high-quality economic development. At the same time, it emphasizes the important role of fiscal decentralization in regulating the relationship between tax reduction and fee reduction and local financial risks, and puts forward corresponding policy suggestions.